Rainfall Variabilty, Climate Finance and Gender Inequality: A Zoom in on Sub-saharan Africa Women - Doku, Isaac (International Journal of Economics and Financial Issues, 2024)
Sustainable Development Goal (SDG)-10 opines that all countries should reduce inequality (being it gender, income, regional or emission inequality) by 2030. However, the exacerbating effect of climate variability seems to widen gender inequality in developing countries such as Sub-Saharan Africa. It is on this backdrop that the UNFCCC mentioned the need for gender mainstreaming in raising climate finance to support developing countries. The main purpose of the study is to find out whether climate finance and rainfall variability impacts gender inequality among 46 Sub-Saharan Africa countries. Data was analysed using system generalised method of moment, to deal with the endogeneity problem inherent in the model. Sensitivity of the estimates was carried out to test the robustness of our results using panel quantile regression. The findings indicate that, SSA countries experiencing high rainfall variability are facing worsening gender inequality both in the short-run and long-run. For climate finance, it showed a significant gender equality strengthening effect in SSA both in the short-run and long-run. This indicates that, CF geared toward developing countries is not only helping mitigate and adapt to climate change, but bridging the gender gap too. Based on that, several policy implications are discussed.